Local identity in development visions (Revista LIDER, 2020)
This article seeks to reconstruct the relationship that has been established between notions of development and local territorial identity. To do this, the ways in which territorial identity has been understood and evaluated from difrerent development perspectives and strategies are explored. The period under consideration begins with the consolidation of the social sciences and development economics following the Second World War, and concludes with current debates that refer to the globalisation process. This review highlights national modernisation projects, the culturalist point of view, the perspectives on endogenous development and Marshallian districts, the focus on globalised competitiveness and the position of local resistance. In each of these, considerations relating to local spaces, and their identities and cultures are emphasised. As is revealed in the article, these considerations are based on different perspectives and value positions which are, in some cases, contradictory. Finally, returning to issues that have been raised previously, some reflections are shared on the most adequate ways for understanding and evaluating territorial identity in relation to the development of local spaces.